Structural causes of the global financial crisis: A critical assessment of the "New Financial Architecture" - James Crotty (University of Massachusetts, Department of Economics, 2008)
The main thesis of this paper is that the ultimate cause of the current global financial crisis is to be found in the deeply flawed institutions and practices of what is often referred to as the New Financial Architecture (NFA) a globally integrated system of giant bank conglomerates and the so-called shadow banking system of investment banks, hedge funds and bank-created Special Investment Vehicles. The institutions are either lightly and badly regulated or not regulated at all, an arrangement defended by and celebrated in the dominant financial economics theoretical paradigm the theory of efficient capital markets. The NFA has generated a series of ever-bigger financial crises that have been met by larger and larger government bailouts. After a brief review of the historical evolution of the NFA, the paper analyses its structural flaws. The problems discussed in order are: 1) the theoretical foundation of the NFA the theory of efficient capital markets is very weak and the celebratory narrative of the NFA accepted by regulators is seriously misleading; 2) widespread perverse incentives embedded in the NFA generated excessive risk-taking throughout financial markets; 3) mortgage-backed securities central to the boom were so complex and nontransparent that they could not possibly be priced correctly; their prices were bound to collapse once the excessive optimism of the boom faded; 4) contrary to the narrative, excessive risk built up in giant banks during the boom; and 5) the NFA generated high leverage and high systemic risk, with channels of contagion that transmitted problems in the US subprime mortgage market around the world. Understanding the profound problems of the NFA is a necessary step toward the creation of a new and improved set of financial institutions and practices likely to achieve core policy objectives such as faster real sector growth with lower inequality.
Keywords: 330; Finanzmarktkrise; Bankensystem; Hedgefonds; Investmentbank; Kritik; Internationaler Finanzmarkt; Reform